Opiate treatment in the criminal justice system: a review of crimesolutions.gov evidence rated programs - Miller, J. Mitchell (American journal of criminal justice, 2016)
As drug control policy reform trends toward marijuana decriminalization, focus will shift to opiate enforcement which, in turn, accentuates substance abuse treatment. While the national offender reentry movement has effected widespread implementation of programming for co-occurring substance abuse and mental health disorders, the practice of Medicated Assisted Treatment (MAT) is nonstandard throughout the criminal justice system despite its evidence based status. This paper observes MAT delivered within and by the criminal justice system as indicated by evidence rated programs and practices listed in the national criminal justice evidence based registry crimesolutions.gov. Observation of these programs’ treatment orientation, client populations, delivery settings, and operational status inform discussion for additional MAT implementation and program registry augmentation.